ANALYSIS OF CHARACTER EDUCATIONAL VALUES IN FOLKLORE AND THE RELEVANCE IN THE FORMATION OF STUDENT’S CHARACTER IN VOCATIONAL HIGH SCHOOL - Agustina, I Wayan; Sutama, I Made; Rasna, I Wayan (Universitas Pendidikan Ganesha, 2019)
This study aimed to (1) describe the values of character education contained in the folklore that used as subject material in Ganesha Vocational High School and (2) the relevance of the values of character education in the folklore in the development of student character. The design of this research is descriptive-qualitative. The subjects of this study are 10 folklores used in Ganesha Vocational High School and teachers of Indonesian subjects in Ganesha Vocational High School. The object of this study is the values of character education contained in the folklore and its relevance to the formation of student characters. Data collection methods used are documentation and interview method. Data analysis is done descriptively-qualitative. At the data reduction stage, identification stage is performed, data matching the problem is observed and classified and at the conclusion draw stage. The results showed that from ten folklore stories analyzed there are values of character education as follows; (1) religious (faith, piety, and thanksgiving); (2) responsibility; (3) social concern (public interest, helpers, willing to sacrifice, cooperation, sharing, and loving); (4) honest; (5) curiosity; (6) the spirit of nationality; (7) love the homeland; (8) independent; (9) discipline; (10); love peace; (11) hard work; (12) creative; (13) friendly / communicative; (14) tolerance; (15) appreciate achievement; (16) care about the environment; (17) like to read; (18) democratic. The results of interviews with teachers of Indonesian subjects in Ganesha Vocational High School, folklore contain the values of advice that can be used as teaching materials, so it has relevance for the development of student character. The conclusion of this study shows the value of characters contained in the story of the people of the Indonesian archipelago is very relevant to be a mirror in everyday life.